Channel‐independent 3D‐EXIT chart‐based path scheduling for serially concatenated decoders. (19th August 2016) - Kayani, Atiqa; Khan, Asif; Ullah, Irfan; Khattak, Shahid
Summary: In this paper a generic method for determining optimal activation cycle scheduling for serially concatenated decoders using three‐dimensional Extrinsic Information Transfer charts is proposed. The complexity of a turbo decoding receiver can be reduced considerably by adopting an optimal activation cycle within the component decoders. However, this optimum scheduled path varies with channel conditions for a given modulation and coding scheme. Thus a real‐time evaluation of the activation path is required, which results in an added computational overhead and storage requirement. Therefore, a channel‐independent method of optimal activation path scheduling using three‐dimensional extrinsic information transfer chart analysis has been proposed where the activation cycle needs to be evaluated once offline and stored as lookup tables as a function of an appropriate compression parameter. The average mutual information of the codeword has been adopted as this compression parameter. It has been demonstrated that the proposed reduced complexity receiver's performance is very close to the more complex conventional fixed activation cycle schemes and superior to the signal to noise ratio‐based dynamic scheduling schemes. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Complexity of an iterative decoding process can be reduced considerably by adopting an optimal activation path within component decoders. In this paper, a channel‐independent method of optimal path scheduling using three‐dimensional Extrinsic Information Transfer chart analysis has been proposed where the activation cycle needs to be evaluated once offline and stored as lookup table as a function of appropriate compression parameter. The average mutual information of the codeword has been proposed as this compression parameter.